IL-6 signaling in macrophages is required for immunotherapy-driven regression of tumors. Issue 4 (20th April 2021) - Beyranvand Nejad, Elham; Labrie, Camilla; van Elsas, Marit J; Kleinovink, Jan Willem; Mittrücker, Hans-Willi; Franken, Kees L M C; Heink, Sylvia; Korn, Thomas; Arens, Ramon; van Hall, Thorbald; van der Burg, Sjoerd H
Abstract : Background: High serum interleukin (IL-6) levels may cause resistance to immunotherapy by modulation of myeloid cells in the tumor microenvironment. IL-6 signaling blockade is tested in cancer, but as this inflammatory cytokine has pleiotropic effects, this treatment is not always effective. Methods: IL-6 and IL-6R blockade was applied in an IL-6-mediated immunotherapy-resistant TC-1 tumor model (TC-1.IL-6) and immunotherapy-sensitive TC-1.control. Effects on therapeutic vaccination-induced tumor regression, recurrence and survival as well on T cells and myeloid cells in the tumor microenvironment were studied. The effects of IL-6 signaling in macrophages under therapy conditions were studied in Il6ra fl/fl ×LysM cre+ mice. Results: Our therapeutic vaccination protocol elicits a strong tumor-specific CD8 + T-cell response, leading to enhanced intratumoral T-cell infiltration and recruitment of tumoricidal macrophages. Blockade of IL-6 signaling exacerbated tumor outgrowth, reflected by fewer complete regressions and more recurrences after therapeutic vaccination, especially in TC-1.IL-6 tumor-bearing mice. Early IL-6 signaling blockade partly inhibited the development of the vaccine-induced CD8 + T-cell response. However, the main mechanism was the malfunction of macrophages during therapy-induced tumor regression. Therapy efficacy was impaired in Il6ra fl/fl ×LysM cre+ but not cre-negative control mice, while no differences in the vaccine-induced CD8 + T-cell response were found between these mice. IL-6 signaling blockade resulted in decreased expression of suppressor of cytokine signaling 3, essential for effective M1-type function in macrophages, and increased expression of the phagocytic checkpoint molecule signal-regulatory protein alpha by macrophages. Conclusion: IL-6 signaling is critical for macrophage function under circumstances of immunotherapy-induced tumor tissue destruction, in line with the acute inflammatory functions of IL-6 signaling described in infections.